Single versus combination antibiotic therapy in adults hospitalised with community acquired pneumonia. Issue 5 (16th October 2012) - Rodrigo, Chamira; Mckeever, Tricia M; Woodhead, Mark; Lim, Wei Shen; ,
Abstract : The benefits of β-lactam/macrolide combination therapy over β-lactam therapy alone for the treatment of hospitalised community-acquired pneumonia (CAP) in relation to pneumonia severity are uncertain. We studied 5240 adults hospitalised with CAP from 72 secondary care trusts across England and Wales. The overall 30-day inpatient (IP) death rate was 24.4%. Combination therapy was prescribed in 3239 (61.8%) patients. In a multivariable model, combination therapy was significantly associated with lower 30-day IP death rate in patients with moderate-severity CAP (adjusted OR 0.54, 95% CI 0.41 to 0.72) and high-severity CAP (adjusted OR 0.76, 95% CI 0.60 to 0.96) but not low-severity CAP.